1992
DOI: 10.1111/j.1432-1033.1992.tb16685.x
|View full text |Cite
|
Sign up to set email alerts
|

Priming of human polymorphonuclear leukocytes with granulocyte‐macrophage colony‐stimulating factor involves protein kinase C rather than enhanced calcium mobilisation

Abstract: Pretreatment of human polymorphonuclear leukocytes with the recombinant human granulocytemacrophage colony-stimulating factor (rhGM-CSF) enhances leukotriene biosynthesis in response to a receptor agonist (e.g. N-formyl-methionyl-leucyl-phenylalanine, fMLP) or a Ca2+-ionophore (e.g. ionomycin). This priming effect could be traced back to an elevated release of arachidonic acid from the phospholipid pools and hence an increased leukotriene biosynthesis by 5-lipoxygenase.Preincubation of polymorphonuclear leukoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Studies in conditioned HL-60 cells and in GM-CSF-conditioned human neutrophils have not demonstrated regulation of 5-lipoxygenase mRNA expression (9,19). Many previous studies have addressed the regulation of 5-lipoxygenase activity and, depending on the cell type and the duration of study, have reported changes at the level of arachidonic acid release (17,(31)(32)(33), 5-lipoxygenase (9,19,21,34), or FLAP (10,20). In our model of primary cell isolates conditioned with lectin-activated lymphocyte supernatant, we have found regulation of 5-lipoxygenase activity at the level of protein and mRNA expression of both 5-lipoxygenase and FLAP, but found no increase in arachidonic acid release.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in conditioned HL-60 cells and in GM-CSF-conditioned human neutrophils have not demonstrated regulation of 5-lipoxygenase mRNA expression (9,19). Many previous studies have addressed the regulation of 5-lipoxygenase activity and, depending on the cell type and the duration of study, have reported changes at the level of arachidonic acid release (17,(31)(32)(33), 5-lipoxygenase (9,19,21,34), or FLAP (10,20). In our model of primary cell isolates conditioned with lectin-activated lymphocyte supernatant, we have found regulation of 5-lipoxygenase activity at the level of protein and mRNA expression of both 5-lipoxygenase and FLAP, but found no increase in arachidonic acid release.…”
Section: Discussionmentioning
confidence: 99%
“…Direct activation of neutrophils by fMLF does not lead to the detectable release of leukotrienes, but priming with GM-CSF, LPS, or TNFα followed by fMLF stimulation significantly increases LTB 4 release (see Table 1; DiPersio et al, 1988a; Schatz-Munding and Ullrich, 1992; Palmantier et al, 1994; Seeds et al, 1998; Zarini et al, 2006). All three of these priming agents activate PLA 2 and increase AA release without increasing intracellular Ca 2+ (DiPersio et al, 1988b; Schatz-Munding and Ullrich, 1992; Zarini et al, 2006).…”
Section: Phenotypic Changes During Primingmentioning
confidence: 99%
“…All three of these priming agents activate PLA 2 and increase AA release without increasing intracellular Ca 2+ (DiPersio et al, 1988b; Schatz-Munding and Ullrich, 1992; Zarini et al, 2006). The elevation in available AA substrate leads to prolonged activation of 5-LO and enhanced production of downstream lipid mediators (Surette et al, 1993, 1998; Doerfler et al, 1994).…”
Section: Phenotypic Changes During Primingmentioning
confidence: 99%
“…Growth factors, cytokines, phorbol esters, LPS, and EBV have been identified and characterized as priming agents [22]. GM-CSF and TNF-␣ priming has been studied widely in neutrophils [23][24][25][26][27][28], and it has been implicated in an enhanced endogenous generation of AA [23,24,26,27]. Furthermore, GM-CSF has been shown to enhance LT synthesis, also when exogenous substrate was used to circumvent cPLA 2 activity [22,29].…”
Section: -Lomentioning
confidence: 99%